A Study of 19th Century Ashrāf Perspective of the Muslims of South Asia (Al-Qamar, 2018)
Modern approaches on social cohesion and identification confirm that the Ashrāf community of 19th century United India shared a number of commonalities based on interaction, goals, interdependence in relation, structure and unity; and their sense to improve their social and political conditions and their response in the form of socio-political measures, manifested in their involvement in the promotion of literary and political organizations is the field of equal interest for sociologists, anthropologists as well as historians. The ashrāf group or community of South Asia, as term evolved through the historical process, developed more cohesion and their efforts were marked under the extensive banner of the Aligarh Movement and were considered as ‘prelude’ to the formation of their significant political organization—the All-India Muslim League (AIML) in the start of 20th century. The research paper in hand deals with this very ashrāf perspective of the Muslims of South Asia.
Keywords: Ashrāf Muslims; South Asia; Sir Syed; Jinah